Characterization of glued laminated panels produced with strips of bamboo (Guadua magna) native from the Brazilian Cerrado - Teixeira, Divino Eterno; Bastos, Rodrigo Pinheiro; Almeida, Sergio Alberto de Oliveira (Cerne, 2015)
Panels were produced with strips of bamboo (Guadua magna) in layers crossed at angles of 90° and bonded with phenol-formaldehyde or PVA based resin, glued in three and five plies. The panels were tested and the physical and mechanical properties determined. The tests were primarily related to the commercial adhesives used as well as the number of layers of bamboo used. The density ranged from 0.690 to 0.768 g.cm-3. Panels bonded with PVA resin showed low mechanical strength, with MOR between 6.7 and 7.8 MPa. Those bonded with phenol-formaldehyde adhesive showed high strength, with modulus of rupture (MOR) ranging from 55.5 to 87.0 MPa, which is excellent for boards similar to wood-based panels. Panels with phenolic resin also had reduced thickness swelling, up to 8.4%. The panels made with three layers showed higher resistance to bending than those made with five layers. © 2015, Federal University of Lavras. All rights reserved.
Caracterização de painéis laminados colados produzidos com taliscas de bambu (Guadua magna) nativo do Cerrado
Keywords: Bamboo; Biomechanics; Cerrado; Density; Phenolic Compound; Physical Property; Resilience; Resin; Wood; Guadua